ANALISIS PENGARUH GENDER, TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, PENGALAMAN AUDITOR DAN KEAHLIAN AUDITOR TERHADAP AUDIT JUDGMENT” (Studi Kasus Pada Kantor Akuntan Publik Di Wilayah Semarang) Oleh: Anindya Nurmalita Dewi 14.05.52.0049 PROGRAM STUDI S1 AKUNTANSI FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS STIKUBANK SEMARANG 2018 - Anindya Nurmalita Dewi, 14.05.52.0049; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2018)
This study examines the analysis of gender influence, compliance stress, task complexity, auditor experience and auditor expertise on audit judgment. This research is a quantitative research, which uses primary data.The population in this study is all auditors who work at Public Accounting Firm (KAP) in Semarang. Sampling was done using convenience sampling method. The instrument of the collection technique used questionnaires distributed directly to the respondents. The number of samples distributed as many as 70 questionnaires, while those used as a further analysis material as many as 60 questionnaires. The results of this study show that gender and auditor experience have a significant positive effect on audit judgment, the pressure of obedience and task complexity have no significant positive effect on audit judgment, and auditor expertise has no significant effect on audit judgment.Keywords: audit judgment, gender, pressure of obedience, task complexity, auditor experience.